Study on the acoustic emission characteristics and damage mechanism of power batteries under electrical load - Peijian Jin; Xinwan Xu; Jinrong Xu; Shuo Yang; Wei Yan; Hui Miao; Shimei Sun (PLoS ONE, 2025)
With the rapid development of new energy vehicles and renewable energy storage systems, the safety and reliability of lithium-ion batteries have garnered significant attention. Therefore, it is crucial to study the aging and damage mechanisms of these batteries, explore effective damage monitoring and characterization methods, and improve their safety. This paper constructs an acoustic emission monitoring platform to assess the aging and damage of lithium-ion batteries during charging and discharging processes. It examines the damage mechanisms of both new and aged batteries under various electrical load conditions. All battery groups produced pulse-type acoustic emission signals during the charging and discharging processes at 1C and 0.5C. The acoustic emission waveforms exhibited a dual-peak characteristic throughout the entire charging and discharging cycles. We observed a pattern in which the time intervals between the waveforms decreased rapidly at first and then stabilized. Based on the frequency characteristics analysis of dual waveforms in acoustic emission signals, we propose a hypothesis regarding the formation mechanism of time differences caused by the propagation of acoustic emission signals from the same source through different media to the sensor. The research findings demonstrate the feasibility of non-destructive acoustic emission monitoring during the charging and discharging processes of lithium-ion batteries, offering new technical support for assessing their health status.